CONCEPTUAL VIEWS OF IBN SINA ON THE CAUSES HEALTH AND ILLNESS (Academicia Globe: Inderscience Research, 2022)
Abu Ali Ibn Sino, the greatest scientist and encyclopedist of the East during the Great Renaissance, wrote his brilliant work “The Canon of Medicine” in 1012-1024. It was a colossal body of medical knowledge, representing one of all on the way to the development of genuine ideas of humanism associated with the struggle for the protection of human health.